(untitled) (Hoboken, 2004)
This comprehensive guide provides you with: Detailed coverage of new tax legislation and IRS rules; Special sections highlighting tax-planning and tax-saving opportunities for investors, business owners, and individuals planning for retirement or other special circumstances; Plain-English explanations of income-reporting rules, tax deductions, and tax credits; Questions and answers that illustrate tax-filing and tax-planning techniques
Keywords: Income tax,Tax planning,Thuế thu nhập,Chính sách thuế; Law and legislation; United States,United States,Hoa Kỳ